2015
DOI: 10.5152/dir.2015.14451
|View full text |Cite
|
Sign up to set email alerts
|

The fate of abstracts presented at Turkish national radiology congresses in 2010-2012

Abstract: R adiology meetings provide a significant channel for exchanging scientific information. Abstract presentations at national meetings allow a rapid transfer of knowledge in summarizing current research and focusing future research endeavors (1)(2)(3)(4)(5). In spite of the fact that many studies are of sufficient value for presentation in these sessions, only the most instructive and highest quality studies are worthy of full-text publication in a peer-reviewed journal (2). The rate of publication may be consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 12 publications
4
33
2
Order By: Relevance
“…In the current study, the publication rate of prospective studies was the highest, which is similar to the findings of Beker-Acay et al indicating a higher publication rate for prospective studies (4). In contrast, Yoon et al reported higher publication rates for retrospective studies (20).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In the current study, the publication rate of prospective studies was the highest, which is similar to the findings of Beker-Acay et al indicating a higher publication rate for prospective studies (4). In contrast, Yoon et al reported higher publication rates for retrospective studies (20).…”
Section: Discussionsupporting
confidence: 73%
“…Consistently, other similar investigations have also demonstrated that the publication rate was comparatively higher for oral presentations (15). Dossett et al (19) and Beker-Acay et al (4) asserted that oral presentations have significantly greater chance to be published in journals. It may be related to higher quality standards of both reviewers and presenters for oral presentations than poster presentations.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…7,8 A wealth of studies documenting the rates of publication following abstract submission exists, and such studies have often been used as a marker of conference quality both within a particular specialty and across specialties. 3,6,[8][9][10][11][12] The most recent systematic review 6 reports a weighted mean publication rate following a conference presentation of 44.5%; however, the publication rates for individual conferences can vary substantially (8%-81%). With respect to vascular surgery, the Vascular Society of Great Britain and Ireland Annual Meeting of 2001 and 2002 reported mean publication rates of 59.4%, whereas the Canadian Cardiovascular Congress has reported mean publication rates of 24.1%.…”
mentioning
confidence: 99%